Pseudo compact almost automorphic solutions to a family of delay differential equations - Zheng Feng-Xia; Li Hong-Xu (Demonstratio Mathematica)
In this article, a family of delay differential equations with pseudo compact almost automorphic coefficients is considered. By introducing a concept of Bi-pseudo compact almost automorphic functions and establishing the properties of these functions, and using Halanay’s inequality and Banach fixed point theorem, some results on the existence, uniqueness and global exponential stability of pseudo compact automorphic solutions of the equations are obtained. Our results extend some recent works. Moreover, an example is given to illustrate the validity of our results.